Demographic and Psychosocial Predictors of Acute Perioperative Pain for Total Knee Arthroplasty - Maya L Roth; Dean A Tripp; Mark H Harrison; Michael Sullivan; Patricia Carson (Pain Research and Management)
BACKGROUND: As the North American population ages, the prevalence of knee osteoarthritis and the surgical interventions (ie, total knee arthroplasty [TKA]) aimed at correcting pain and disability will also rise proportionally. Therefore, efforts to better understand the factors associated with surgical outcomes are warranted. To date, no studies have examined the impact of psychosocial factors on acute postoperative TKA pain.